Application of PROMETHEE method for green supplier selection: A comparative result based on preference functions - Lazim Abdullah; Waimun Chan; Alireza Afshari (Journal of Industrial Engineering International, 2019)
The PROMETHEE is a significant method for evaluating alternatives with respect to criteria in multi-criteria decision-making problems. It is characterized by many types of preference functions that are used for assigning the differences between alternatives in judgements. This paper proposes a preference of green suppliers using the PROMETHEE under the usual criterion preference functions. Comparable results are presented to check the effect of different preference functions on the final preference. Seven economical and environmental criteria, four suppliers and five decision makers were the main structures in the green supplier selection problem. Data were collected via personal communication with decision makers using five-point Likert scale. The algorithm of PROMETHEE under usual criterion function was implemented, and the results show that supplier A1 is the most preferred alternative. Comparative results also show that supplier A1 is the most preferred alternative despite the difference in preference functions used.
Keywords: 650; Preference function; Decision making; Green supplier selection; Outranking; PROMETHEE